2006
DOI: 10.1002/bit.21210
|View full text |Cite
|
Sign up to set email alerts
|

Detection of S100 protein from prostatic cancer patients using anti‐S100 protein antibody immobilized on POS‐PVA discs

Abstract: The S100 proteins have been extensively used as cancer biomarkers. The objectives of the present work were to immobilize the antibody anti-protein S100 to a net of semi-interpenetrated of polysiloxane and polyvinyl alcohol (POS-PVA discs), to investigate its capacity to capture S100 protein from serum and to quantify it by ELISA in sera from patients with prostatic adenocarcinoma (n = 15) and healthy individuals (n = 10). Also these values were compared to the S100 protein expression in the prostatic tissue th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These findings suggest, while S100A6 is commonly overexpressed in OS, loss of its expression may correlate with a metastatic phenotype. A cluster of 16 types of S100 genes is located on 1q21, which is frequently amplified or rearranged [25,35,37,71,158,190,209]. S100 proteins constitute a group of nearly 20 proteins that contain wellconserved EF-hand calcium-binding domains [209].…”
Section: Os Metastasis-associated Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest, while S100A6 is commonly overexpressed in OS, loss of its expression may correlate with a metastatic phenotype. A cluster of 16 types of S100 genes is located on 1q21, which is frequently amplified or rearranged [25,35,37,71,158,190,209]. S100 proteins constitute a group of nearly 20 proteins that contain wellconserved EF-hand calcium-binding domains [209].…”
Section: Os Metastasis-associated Genesmentioning
confidence: 99%
“…S100 proteins constitute a group of nearly 20 proteins that contain wellconserved EF-hand calcium-binding domains [209]. Several S100 proteins have been associated with human cancers [25,35,37,71,158,190,209].…”
Section: Os Metastasis-associated Genesmentioning
confidence: 99%
“…All the S100 proteins will form homodimer and heterodimer [1] to play a role. At present, it has been reported that abnormal expression of S100 protein is related to multiple tumors, such as thyroid cancer, [10,11] renal carcinoma, [12][13][14] melanoma, [15][16][17] breast cancer, [18,19] colorectal cancer, [20][21][22] bladder cancer, [23,24] prostatic cancer, [25,26] lung cancer, [27][28][29] gastric cancer [30,31] and so on. [8] Each EF-hand-shape structure domain is composed of two spirals (E spiral and F spiral) and a link in the middle; Ca 2+ is connected with this link, [9] and the two hand-shape structure domains are connected by a hinge region.…”
mentioning
confidence: 99%